Improvement of the Logical Intelligence Through Media Kolak (Collage Numbers) Based on Local Wisdom on Early Childhood - Novi Ade Suryani; Mimpira Haryono (LPPM Universitas Pahlawan Tuanku Tambusai, 2018)
This study aims to improve logical intelligence through media kolak (collage numbers) based on local wisdom in early childhood in PAUD Mawar Al Barokah, Padang Serai Village, Kampung Melayu District, Bengkulu City. The procedure for carrying out this research was carried out using two cycles. Each cycle consists of four stages, namely planning, acting, observing, and reflecting. Each cycle also consists of two meetings, where each meeting has three assessments 1). Know the shape of objects, 2). Know the concept of numbers, and 3). Calculate the number of objects. The results showed an increase that the end of the second cycle was higher than the end of the first cycle in the category of Very Good Developing Children (BSB), namely at the stage of recognizing the shape of objects by 84%, knowing the concept of numbers by 64%, and at the stage of calculating the number of objects of 72 %. In addition, from the learning process it seems fun by using natural materials that are easily available, students become more active, enthusiastic, and creative. Thus, learning through media kolak (collage numbers) based on local wisdom can be used by teachers to improve logic intelligence in early childhood.